Three-Dimensional Echocardiography Compared With Computed Tomography to Determine Mitral Annulus Size Before Transcatheter Mitral Valve Implantation. (June 2016) - Mak, George J.; Blanke, Philipp; Ong, Kevin; Naoum, Christopher; Thompson, Christopher R.; Webb, John G.; Moss, Robert; Boone, Robert; Ye, Jian; Cheung, Anson; Munt, Brad; Leipsic, Jonathon; et al.
Abstract : Background—: Previously, through the use of computed tomography (CT), it has been proposed that D-shaped versus saddle-shaped mitral annulus (MA) segmentation is more biomechanically appropriate to determine transcatheter mitral valve implantation size and eligibility. Methods and Results—: Forty-one patients with severe mitral regurgitation being considered for transcatheter mitral valve implantation who had undergone cardiac CT and 3-dimensional transesophageal echocardiography (3D-TEE) were retrospectively evaluated. A standardized segmentation protocol for the D-shaped MA was developed using Philips Q-Laboratory mitral valve quantification software. MA dimensions were compared using Spearman's rank correlation and Bland–Altman analysis. Inter- and intraobserver agreement was quantified by intraclass correlation coefficient and Bland–Altman analysis. Mean age was 77±14 years; 71% male (n=29); mitral regurgitation pathogenesis was functional in 54% (n=22) and myxomatous in 46% (n=19). Mean MA area and circumference by 3D-TEE and CT were 11.3±2.7 versus 11.4±3.0 ( P =0.67) and 124.1±15.6 versus 123.9±15.5 ( P =0.79), respectively, with excellent correlation between modalities ( r =0.84 and r =0.86; P <0.0001) and no systematic bias (−0.20±1.8 cm 2 [−3.7 cm 2 ; 3.3 cm 2 ], 0.37±9 mm [−18.0 mm; 17.27 mm]). Mean septal-to-lateral and inter-trigone distances by 3D-TEE and CT were 33.2±4.7 versus 32.5±4.4 ( P =0.24) and 31.7±3.5 versus 32.6±3.6 ( P =0.06), respectively, with good correlation ( r =0.69 and r =0.71; P <0.0001) and no systematic bias (0.77±3.8 mm [−6.7 mm; 8.2 mm], −1.5±3.1 mm [−4.6 mm; 7.6 mm]). There was excellent intra- and interobserver agreement according to intraclass correlation coefficients >0.90 for all parameters. Conclusions—: Similar to cardiac CT, 3D-TEE allows for D-shaped MA segmentation with no systematic difference in MA dimensions between modalities. This study supports the utilization of 3D-TEE as a complementary tool to CT assessment of the D-shaped MA to determine transcatheter mitral valve implantation size. Abstract : Supplemental Digital Content is available in the text.